HUBUNGAN SUMBER INFORMASI POSYANDU DAN DUKUNGAN KELUARGA DENGAN PARTISIPASI PENIMBANGAN BALITA DI WILAYAH KERJA PUSKESMAS KELURAHAN KEBAYORAN LAMA UTARA TAHUN 2020 - Fitria Indah Akhirunnisya (2020)
Children under five weighing is one of program with purpose to prevent malnutrition. But the participation still low. The purpose of this research is to know relation of Posyandu information source and family support with children under five weighing participation in the working areas of Puskesmas Kelurahan Kebayoran Lama Utara year 2020. This research is using quantitative research with cross sectional study. The population is a mother who has a child aged 6-59 months, with a sample size of 101 people. Analysis with chi-square. And the result of data analysis show that there is relation between family support with children under five weighing participation (p=0,000). Therefore health promotion and motivation is needed to improve children under five weighing participation.